Evaluation of Bystander Infection of Oncolytic Virus using a Medium Flow Integrated 3D In Vitro Microphysiological System. Issue 2 (11th December 2019) - Lee, Sang Woo; Lee, Kyoung Jin; Jeong, Soo Yeon; Joo, Chul Hyun; Lee, Heuiran; Jeong, Gi Seok
Abstract: Replicable oncolytic viruses (OVs) induce tumor cell lysis and release viral progeny. The released progeny virions and cell debris can spread within surrounding tumor cells or blood vessels. These released molecules may also induce bystander damage in additional tumor cells through spreading within surrounding tumor cells or blood vessels. However, this effect has not been clearly demonstrated due to the difficulty of direct observation. Here, the bystander infection of OVs by vessel delivery and selective infection in 3D multicellular tumoroids (MCTs) in an in vitro microphysiological system (MPS) with integrated medium flow is demonstrated. This study uses replicable vesicular stomatitis virus (VSV)‐green fluorescence protein (GFP) to identify the location of infection in 3D MCTs. Using this MPS, the oncoselective infection by VSV‐GFP and the spreading by delivery of OVs through flow via block‐to‐block linkage of the primary infected MPS with uninfected 3D MCTs in an integrated MPS is observed. This MPS enables real‐time monitoring and various analysis for the bystander infection of OVs. It is expected that the 3D in vitro MPS can be suitable to investigate the oncoselective spreading and bystander infection of OVs. Abstract : Spreading of oncolytic viruses (OVs) as an anticancer agent offers therapeutic opportunities for both the primary tumor and any apparent or undiagnosed metastatic deposits simultaneously. A well‐defined in vitro 3D microphysiological system that reflects the spreading of OVs into the vessel, such as those occurring in the in vivo microenvironment, can contribute to simulating the assumption of bystander damage and spreading.